Increasing The Capacity of MSME Product Sales Through Sales Promotion Advertisements on Social Media - Suryono, Joko (Jogjakarta Communication Conference (JCC), 2025)
Sales promotion advertisements play an important role in increasing the capacity of MSMEs in terms of product sales and are able to influence purchasing decisions by providing stimulation to potential consumers. Sales promotions have an interesting aspect in stimulating potential consumers by providing discounts, holding contests, flash sales and loyalty programs, which are designed to increase customer interest and involvement. The purpose of the study is to explain the role of sales promotion advertisementsUMKM Astro Distro Fashionon social media to stimulate potential consumers. Types and approaches of research: qualitative descriptive research type, using a case study approach. The object of research in UMKM Astro Distro Fashion, Sragen Regency, Indonesia. Types and sources of research data: (a) narratives from the main data source, namely informants of UMKM Astro Distro Fashion advertising activities; (b) results of observations of MSME sales promotion advertisements on social media. Informants consist of owners and managers of UMKM ADF, creative content for UMKM ADF advertisements, consumers of UMKM ADF. Data Validation: guaranteeing the validity of data with source triangulation, method triangulation. Data analysis techniques: using an interactive inductive logic modelMile and Huberman. Conclusion: Sales promotion advertising can increase the sales capacity of MSME products by increasing their frequency and depth. MSME Astro Distro Fashion carries out sales promotion advertising activities through flash sale strategies, discounts, lottery coupons by paying attention to time, new items, making items go viral quickly, the amount of sales value and risk.